PEMBINAAN DETEKSI DAN INTERVENSI DINI TUMBUH KEMBANG BALITA PADA KADER POSYANDU - Yena Wineini Migang (Unika Santu Paulus Ruteng, 2021)
Stunting is a form of growth failure (growth faltering) due to the accumulation of inadequate nutrition that lasts a long time from pregnancy to 24 months of age. If stunting is not prevented immediately, it will have an impact on the quality of future generations, especially in 2031 the estimated demographic bonus occurs. Stunting can lead to increased morbidity and mortality among children under five. Stunted growth and development. Based on data from the Indonesian Ministry of Health, Directorate General of Public Health, Directorate of Nutrition, Kalimantan, in 2015 the percentage of stunting aged 0-59 months was (38.4%) in 2016 (34.1%) in 2017 (39.0%), 2018 (34%) ) and in 2019 (32%) this is still far from the 2020-2024 RPJM target (19%). The role of Posyandu cadres is really needed to be able to screen the incidence of stunting, and so far this has not been done optimally because of the lack of knowledge about early detection and intervention for the growth and development of children under five. As an effort to prevent stunting, it is necessary to detect and intervene early in child development with instruments that have been determined from the Indonesian Ministry of Health on an ongoing basis, especially during the pre-school age, one of the activities is to provide guidance using instruments for Posyandu cadres. This community service was carried out in 2020 with the subject of cadres at Posyandu Katingan and Melati, Palangka Raya City. The aim of this coaching is so that cadres can detect delays and deviation in growth and development in children so that they can be immediately intervened so that they are given the right therapy.